Liquid Biopsy of Extracellular Microvesicles Predicts Future Major Ischemic Events in Genetically Characterized Familial Hypercholesterolemia Patients. Issue 6 (June 2019) - Suades, Rosa; Padró, Teresa; Crespo, Javier; Sionis, Alessandro; Alonso, Rodrigo; Mata, Pedro; Badimon, Lina
Abstract : Objective—: Circulating microvesicles (cMVs) exert regulatory roles in atherothrombosis. Patients with familial hypercholesterolemia (FH) that are at high risk for premature cardiovascular events (CVEs) have previously shown high levels of cMVs related to disease severity. However, much remains unknown about their value as markers of CVE. We sought to investigate the prognostic cMV signature for future major CVE presentation in patients with FH. Approach and Results—: Liquid biopsies from genetically characterized patients with FH from the SAFEHEART (Spanish Familial Hypercholesterolemia Cohort Study)-cohort without clinical manifestation of disease at entry that were going to suffer a CVE within a mean period of 3.3±2.6 years postsampling (CVE, N=92) and from age/cardiovascular risk factor/treatment-matched patients with FH that did not suffer an event within the same time-period (non-CVE, N=48) were investigated. cMVs were phenotyped by flow cytometry to identify activated parental cells. Patients with CVE had higher number of overall procoagulant annexin V + -cMVs than non-CVE ( P <0.05). Pan-leukocyte-derived and neutrophil-derived cMVs, as well as activated platelet-derived cMVs, were significantly higher in patients with CVE. Baseline number of cMVs derived from lymphocytes, neutrophils, and activated platelets were positively associated with mortality at follow-up ( P <0.05). Patient-risk calculated by classical cardiovascular risk-factor scores did not correlate with cMVs. Inclusion of the cMV signature into the SAFEHEART risk model for patients with FH for the prediction of ischemic events increased the area under the curve from 0.603±0.050 to 0.768±0.042 ( P <0.005). Conclusions—: Patients with FH who are going to suffer a CVE within a mean period of 3.3 years, despite being treated according to guidelines, have ongoing innate immune cell and platelet activation. The proposed cMV signature is a prognostic marker for accelerated atherosclerosis and clinical event presentation in patients with FH. Abstract : Supplemental Digital Content is available in the text.